International transit studies program report on the Fall 1998 mission : revitalizing urban public transport in Australia and New Zealand. - Dunleavy, Tracy E.; United States. Federal Transit Administration; Transit Cooperative Research Program; National Research Council (U.S.). Transportation Research Board; Eno Transportation Foudation ([Washington, D.C.] Transportation Research Board, National Research Council, 1999)
"This TCRP Digest summarizes the ninth mission performed under TCRP Project J-3, "International Transit Studies Program"."
Caption title.
"This digest was prepared by Tracy E. Dunleavy of the Eno Transportation Foundation, Inc. ..."
"Sponsored by the Federal Transit Administration."
December 1999.
Keywords: Urban transportation -- Australia; Urban transportation -- New Zealand